Dividend policy in Turkey: Survey evidence from Borsa Istanbul firms - Baker, H. Kent; Kilincarslan, Erhan; Arsal, Alper Haktan (JAI PRESS INC, 2018)
This study investigates the views of managers of firms listed on the Borsa Istanbul (BIST) on dividend policy. The survey evidence provides general support for Lintner's partial adjustment model, signaling theory, catering, firm life cycle, and bird-in-the-hand hypotheses for explaining cash dividends. The results do not support the agency cost theory, substitution model of dividends, tax-related explanations, transaction cost theory, and residual dividend policy. The findings suggest that after implementing major economic and structural reforms and abolishing a mandatory dividend payment requirement, BIST managers follow similar dividend policy factors and patterns of dividend policy as managers in more developed countries.
Keywords: CORPORATE-OWNERSHIP; STOCK-EXCHANGE; MANAGERS; DETERMINANTS; PERCEPTION; VIEWS; WORLD; Business & Economics